The effect of GeoGebra software–supported mathematics instruction on eighth‐grade students' conceptual understanding and retention - Birgin, Osman; Uzun Yazıcı, Kübra (Journal of computer assisted learning, 2021)
The aim of this study was to investigate the effect of using dynamic geometry software (GeoGebra) on the eighth‐grade students' conceptual understanding and the retention of learning regarding linear equations and slope. In this study, a quasi‐experimental design with pre‐test, post‐test and delayed post‐test was employed. This study was conducted with 52 eighth‐grade Turkish students (experimental group, n = 25; control group, n = 27). While GeoGebra software‐supported instruction was carried out in the experimental group, textbook‐based direct instruction was continued in the control group. Data were collected with the conceptual understanding test (CUT) which consists of 38 questions including open‐ended, multiple choice and fill in the blanks. CUT was applied to the experimental and control groups as a pre‐test and post‐test at both the beginning and the end of the instruction, respectively. Seven weeks after the instruction, CUT was applied to both groups as a retention test. Data were analysed through SPSS 17.0 statistical software by using a t‐test and ANCOVA test. It was indicated in the study results that GeoGebra software‐supported instruction for eighth‐grade students regarding linear equations and slope did significantly improve both their conceptual understanding and retention of learning in comparison to textbook‐based direct instruction. Lay Description What is already known about this topic? The subject of functions and their graphs are the basis of many mathematical concepts and subjects such as logarithm, limit, derivative and integral. It is indicated in many studies that middle‐grade students have some misconceptions and difficulties in learning the concept of a straight line and slope. It was determined in previous studies conducted at different grade level that using dynamic geometry software (DGS) increases students' mathematics achievement according to traditional instruction. There is a need for research investigating the effect of using GeoGebra software on eighth grade students' conceptual understanding and retention of learning regarding linear equations and slope. What this paper adds? A quasi‐experimental design with pre‐test, post‐test and delayed post‐test was conducted. Using GeoGebra software had positive effects on eighth‐grade students' conceptual understanding regarding linear equations and slope. The learning environment with GeoGebra software increased the retention of learning. The implications of study findings for practitioners This research provided evidence regarding the effects of using GeoGebra software on eighth‐grade students' conceptual understanding and retention of learning in mathematics. In future studies, the long‐term effects of GeoGebra on other mathematics topics and other learning outcomes within similar settings should be examined.